The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.2337/ds17-0045
|View full text |Cite|
|
Sign up to set email alerts
|

Multidisciplinary Team–Based Obesity Treatment in Patients With Diabetes: Current Practices and the State of the Science

Abstract: IN BRIEF Rates of obesity and diabetes are growing, as are their costs. Because the two diseases share many key determinants, the paradigms for their treatment overlap. For both, optimal treatment involves a multidisciplinary team following the Chronic Care Model of health care delivery. Combined treatment programs that include 1) a low-calorie diet individualized to patients’ preferences, 2) structured exercise that is also tailored to each patient, and 3) psychotherapy induce the largest weight changes in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 84 publications
(75 reference statements)
0
22
0
Order By: Relevance
“…A meta‐analysis of 29 weight loss interventions in the United States, with at least a 2‐year follow‐up period, found that over a quarter of lost weight had been regained at 1 year and 80% of lost weight was regained by 5 years 11,12 . At the individual level, a multidisciplinary team approach with input from medical, dietetic, exercise, and behavioural experts is recommended for chronic disease management, weight loss, and long‐term weight maintenance 7,8,12–17 . The multidisciplinary approach allows each team member to deliver regular and ongoing care and support within their specific expertise.…”
Section: Introductionmentioning
confidence: 99%
“…A meta‐analysis of 29 weight loss interventions in the United States, with at least a 2‐year follow‐up period, found that over a quarter of lost weight had been regained at 1 year and 80% of lost weight was regained by 5 years 11,12 . At the individual level, a multidisciplinary team approach with input from medical, dietetic, exercise, and behavioural experts is recommended for chronic disease management, weight loss, and long‐term weight maintenance 7,8,12–17 . The multidisciplinary approach allows each team member to deliver regular and ongoing care and support within their specific expertise.…”
Section: Introductionmentioning
confidence: 99%
“…57 Low fat diets, where fat intake is reduced by 10% and protein intake is increased to 25%, have been shown to satiate patients using fewer overall calories. 58,59 Despite these findings, no specific plan has shown to be more effective so long as an energy intake deficit occurs. 54 With regards to food content (eg, low vs high fat), weight loss trumps any negative effects of individual dietary components.…”
Section: Dietary Interventionsmentioning
confidence: 99%
“…Of note, exercise without dietary restrictions is able to achieve only 3–5% weight loss in patients with obesity [ 16 ]. A wide variety of dietary intervention patterns, such as Mediterranean diet, low carbohydrate diet, low-fat diet and ketogenic diet (KD), which significantly differ in the proportions of macronutrients, have been extensively evaluated in clinical trials and displayed great efficacy in reducing body weight and in improving metabolic abnormalities in obese patients [ 17 19 ]. On the other hand, bariatric surgery is a highly effective strategy for weight loss and comorbidities improvement in morbidly obese patients when life style intervention fails.…”
Section: The Challenges Of Obesity Treatmentmentioning
confidence: 99%